Written Languages in Wallachia during the Reign of Neagoe Basarab (1512–1521) - Knoll, Vladislav (Studia Ceranea, 2021)
The reign of Neagoe Basarab (1512–1521) represented one of the cultural peaks of Wallachian history. Using the written sources preserved from this period, we tried to present the written Slavonic varieties and other languages (Romanian and Latin) that were used in that period. The Slavonic varieties are examined according to three criteria: spelling, morphosyntax and vocabulary. The standard variety (Church Slavonic) and the specific local written variety we may call Wallachian Slavonic, most purely represented by the epistolography, are opposed in morphosyntax and vocabulary. Both types of varieties are competing in acts and some colophons, eventually other original texts. The spelling criterion permits us to distinguish up to four Church Slavonic varieties, whence two are international ones (Moldavian Trinovitan (Tărnovo) variety and Resavian variety) and two comprise local adaptations – the Trinovitan variety influenced by the Wallachian liturgical pronunciation and the administrative Church Slavonic representing a simplified combination of both Trinovitan and Resavian norms. The Romanian language (written in Cyrillic) is not represented just by its oldest dated coherent text (Neacşu’s letter), but also by frequent penetrations mainly in the documents. The main common feature of the Latin documents with other Wallachian varieties is the presence of the proper names.